2004
DOI: 10.1002/14651858.cd001857.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing injuries in problem drinkers

Abstract: Gallant 1968 {published and unpublished data} Gallant DM, Bishop MP, Camp E, Tisdale C. A six-month controlled evaluation of metronidazole (Flagyl) in chronic alcoholic patients. Current Therapeutic Research 1968;10(2):82-7. Gentilello 1999 {published data only} Gentilello LM, Rivara FP, Donovan DM, et al. Alcohol interventions in a trauma center as a means of reducing the risk of injury recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 45 publications
2
11
1
3
Order By: Relevance
“…Thus, the heterogeneity of this sample supports the external validity as well as the generalizability of our findings. That we did not find group differences on alcohol problems is somewhat puzzling, especially as an earlier study of MI with a similar age group showed an impact on alcohol-related negative consequences, but not consumption, after 6 months [16], although this inconsistency in findings across studies is not unusual [34]. It is possible that the personalized feedback had a direct harm reduction effect, whereas the in-person MI was necessary to affect alcohol use.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, the heterogeneity of this sample supports the external validity as well as the generalizability of our findings. That we did not find group differences on alcohol problems is somewhat puzzling, especially as an earlier study of MI with a similar age group showed an impact on alcohol-related negative consequences, but not consumption, after 6 months [16], although this inconsistency in findings across studies is not unusual [34]. It is possible that the personalized feedback had a direct harm reduction effect, whereas the in-person MI was necessary to affect alcohol use.…”
Section: Discussioncontrasting
confidence: 55%
“…Agressões sexuais por estranhos, violência nas escolas ou trabalho, ruas, prisões e retiros de idosos constituem a violência comunitária Muitas pesquisas demonstram relação entre o uso de bebidas alcoólicas e comportamento violento [3][4][5][6] . Há facilitação da violência pelo álcool, havendo associação entre estar alcoolizado e participação em homicídios, suicídios, violência domés-tica, crimes sexuais, acidentes de trânsito, tanto como vítima ou perpetrador destas violências 6,7 . O consumo de bebidas alcoólicas também está associado a afogamentos, delinqüên-cia e diminuição do rendimento escolar 7,8 .…”
Section: Introductionunclassified
“…Há facilitação da violência pelo álcool, havendo associação entre estar alcoolizado e participação em homicídios, suicídios, violência domés-tica, crimes sexuais, acidentes de trânsito, tanto como vítima ou perpetrador destas violências 6,7 . O consumo de bebidas alcoólicas também está associado a afogamentos, delinqüên-cia e diminuição do rendimento escolar 7,8 . Entretanto, a relação entre o consumo de álcool e violência é complexa, pois não existe associação simples e unidirecional 9 .…”
Section: Introductionunclassified
“…Acutely, EtOH causes motor control alterations, ataxia, and vertigo, increasing the risk of accidental injuries, which are responsible for millions of deaths around the world (Dinh-Zarr et al, 2004). Individuals with lower sensitivity to the acute motor impairing effects of EtOH have an increased risk of developing alcohol dependence and abuse (Schuckit, 1994), and infants with subtle delays in motor coordination development may have an increased risk for subsequently developing alcoholism (Manzardo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%